Growth of Copper Indium Telluride (Cuinte2) Thin Films Using Electrochemical Route for Photovoltaic Application - Adhikari, Subash; Chaure, NB (Nepal Journal of Science and Technology, 2012)
Copper indium di-telluride (CuInTe2; CIT) was electrochemically deposited onto indium tin oxide (ITO) substrate using aqueous medium at various electrodeposition conditions like temperature, pH, stirring rate and concentration of the samples. The resulting thin films were characterized using UV-Visible-NIR spectrophotometer, X-ray diffractometer, scanning electron microscopy and energy dispersive X-ray to find out energy band gap, structural properties, surface morphology and the elemental composition in the film respectively. The resulting films showed a polycrystalline nature with band gap varying from 1.27 to 1.89 eV. The elemental composition of the as deposited and annealed sample showed that the films were mostly copper and tellurium rich. The crystallinity of the films improved after annealing for 5 minutes at 350°C but the secondary phase like CuxTe and InxTe could not be recombined completely. DOI: http://dx.doi.org/10.3126/njst.v12i0.6519 Nepal Journal of Science and Technology 12 (2011) 318-323